TANGGUNG JAWAB DINAS PERINDUSTRIAN DAN PERDAGANGAN PROVINSI KALIMANTAN BARAT TERHADAP PERDAGANGAN HELM TANPA LABEL STANDAR NASIONAL INDONESIA DI KOTA PONTIANAK - NIM. A1011161094, NURDIAN NASUTION (Fakultas Hukum Universitas Tanjungpura, 2020)
The Department of Industry and Trade of West Kalimantan Province is one of the technical agencies that foster the economic sector in West Kalimantan. One of the tasks of the Department of Industry and Trade of West Kalimantan Province is to Supervise the Indonesian National Standard Without Helmet Trade in the City of Pontianak which is still widely traded by Business Actors.This study aims to determine how the responsibilities and inhibiting factors of the Department of Industry and Trade of the Province of West Kalimantan on the trade of helmets without Indonesian National Standard Labels in Pontianak City. This type of research is empirical research. The problem approach used is Descriptive Analyst. The data used are primary and secondary data consisting of primary and secondary legal materials. Data collection is done by interview.The results of the study show that the responsibilities of the West Kalimantan Provincial Industry and Trade Office have not been running optimally, this is evidenced by the not yet carrying out Special Supervision and Integrated Supervision of the Periodic Oversight results which have found the existence of the Helm trade without the Indonesian National Standard Label in the City of Pontianak. Keywords: Responsibility, Supervision, Consumer Protection